Effect of temperature on the magnetic properties of Fe3O4 thin films studied by ferromagnetic resonance (FMR) - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2008)
Single crystalline Fe3O4 thin films of 110 angstrom thickness grown on MgO (100) substrate have been investigated by Ferromagnetic Resonance (FMR) technique as a function of temperature between 3 and 300 K. A strong unidirectional (exchange) anisotropy field was detected as evidence from a shift of the resonance field for the r-FC case relative to that for n-FC case at lower temperature. Using a field-induced unidirectional exchange and bulk anisotropy, with the usual magneto-crystalline cubic anisotropy energy, we have simulated both the experimental spectra and angular dependence of resonance field to deduce anisotropy and other magnetic parameters as a function of temperature. Magnetic parameters and Verwey transition for the thin film case were found to shift down to around 90 K from 120 K for bulk sample of the same compound as well. (c) 2008 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: ELECTRON-SPIN-RESONANCE; TRANSITION; ANISOTROPY